A STUDY ON THE IMPLEMENTATION CHALLENGES FOR ERP IN SMEs INKANNIYAKUMARIDISTRICT (International Journal of Food and Nutritional Sciences, 2022)
ERP (Enterprise Resource Planning) is a method for integrating an organization's data andprocedures into a single system. Its fundamental objective is to unite the organization and integratedata and processes from all departments in order to facilitate easy access and a productive work flow.ThecurrentstudyfocusesonthechallengesSME'sintheKanniyakumariDistricthaveinimplementing ERP. 50 SMEs from the Kanniyakumari District were chosen using a simple randomsampling. Their biggest problem is that it is expensive to install and that the staff members lacksufficient information technology skills. SMEs must deploy ERP in order to survive in the globalcompetitivemarketplace.